Kontekstualisasi Jual Beli Pada Masa Klasik dan Modern dalam Tinjauan Hadis - Maulid Ihza Juliandi; Mugiyono; Sulaiman Muhammad Nur (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Buying and selling transactions have undergone significant transformation and advancement. New forms of buying and selling, such as online stores and dropshipping, are now available, facilitating interaction and communication via the internet. This allows people not only to explore knowledge online but also to conduct commercial transactions. One frequently used transaction is the pre-order system. This study aims to understand the hadith on buying and selling and explore how the principles of buying and selling taught in the hadith can be applied in the context of modern transactions, including online buying and selling and pre-order systems. The goal is to ensure that the buying and selling process remains in accordance with Sharia principles and provides fairness to all parties involved. The study employed a qualitative methodology, utilizing literature analysis, referring to the hadith of Sahih Bukhari no. 2239 and relevant books, theses, and articles. The results indicate that traditional Islamic transactions, involving advance payment and later delivery, remain relevant in the digital era. Online buying and selling practices are now popular due to the convenience, speed, and clarity of product specifications offered through e-commerce platforms. After payment, the seller ships the goods within 2-4 days to the agreed-upon address. Salam transactions are permissible under Islamic law and are considered beneficial to society, according to the views of contemporary scholars.